2022
DOI: 10.1002/phar.2747
|View full text |Cite
|
Sign up to set email alerts
|

Examining the clinical impact of rapid multiplex polymerase chain reaction‐based diagnostic testing for bloodstream infections in a national cohort of the Veterans Health Administration

Abstract: Study Objective Bloodstream infections (BSIs) are a significant cause of mortality. Use of a rapid multiplex polymerase chain reaction‐based blood culture identification panel (BCID) may improve antimicrobial utilization and clinical outcomes by shortening the time to appropriate therapy and de‐escalating antibiotics among patients on overly broad‐spectrum empiric therapy. The effect of BCID on clinical outcomes across varying institutional antimicrobial stewardship program (ASP) practices is unclear. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Therefore, further evaluations are warranted for rare target organisms. Second, several previous studies have shown that improving turnaround time through BCID has a positive clinical effect on shortening the time to optimize antibacterial treatment for patients with BSIs, especially those requiring antibiotic susceptibility testing and subsequent molecular screening [ 9 , 25 , 26 ]. However, this study has yet to evaluate the impact of this rapid reporting of results on patient health and health service outcomes in clinical settings, which remains a subject of further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further evaluations are warranted for rare target organisms. Second, several previous studies have shown that improving turnaround time through BCID has a positive clinical effect on shortening the time to optimize antibacterial treatment for patients with BSIs, especially those requiring antibiotic susceptibility testing and subsequent molecular screening [ 9 , 25 , 26 ]. However, this study has yet to evaluate the impact of this rapid reporting of results on patient health and health service outcomes in clinical settings, which remains a subject of further research.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex polymerase chain reaction (mPCR) panels, also known as syndrome panels, are considered a principal technology in the many strategies that integrate tests for multiple pathogens and/or antimicrobial resistance genes into a single test, providing rapid results for multiple targets [ 6 , 7 ]. The introduction of the mPCR panel in clinical microbiology laboratories is expected to improve patient care and clinical workflow, as well as reduce hospitalization costs by reducing diagnosis and decision-making time [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 A recent large retrospective cohort of over 4000 patients within the Veterans Health Administration failed to demonstrate beneficial clinical outcomes. 73 Two RCTs evaluating the clinical impact of mRDTs also failed to detect a difference in mortality, LOS, or hospital readmission; however, the studies were not powered to detect these differences. 38,40 A prospective, randomized, open-label trial (NCT03744728) evaluating the Accelerate Pheno platform compared with the Verigene® BC-GP/GN is ongoing.…”
Section: Future Direc Tionsmentioning
confidence: 99%
“…Overall, antimicrobial consumption will not likely provide the necessary insight into the success of the implementation, nor will review clinical outcomes such as hospital LOS or inpatient mortality. As recently demonstrated within a large Veteran's Affairs population of over 4000 patients with BSI, changes to process metrics such as time to appropriate antimicrobials can be impacted by mRDTs, but 30‐day mortality remained relatively unchanged 73 . Therefore, it is within the AMS program's best interest to evaluate the intervention success based on process metrics such as adherence to guideline recommendations and time to appropriate and optimal therapy.…”
Section: Practical Ams Considerations For Implementing Mrdts Within H...mentioning
confidence: 99%
See 1 more Smart Citation